Inclusión educativa y rincón de lectura en educación inicial I en la Unidad Educativa Particular Vicente Agustín Aguirre Ruíz. Periodo 2023-2024 - Hurtado Patiño, Gabriela Vanessa (2024)
The present research work aims to analyze the educational inclusion and the reading corner in the first year of pre-school education in the Vicente Agustín Aguirre Ruíz Private School. The research approach is qualitative, descriptive non-experimental, the sample was made up of 1 teacher and 15 children aged between 3 and 4 years. The technique used was the semi-structured interview, and an observation form which allowed to corroborate some answers based on two variables: Educational inclusion and reading corner. Then, to obtain the results a triangulation of the data was carried out from which the following results were obtained: It was identified the importance of promoting educational inclusion at the pre-school level by promoting diversity and respecting the individual differences of boys and girls, despite the teacher's willingness, the need for further training to achieve true inclusion was evident. The presence of a reading corner is of great importance for carrying out the different activities, but it is essential to have the appropriate inclusive materials that reflect cultural, ethnic and gender diversity to guarantee an inclusive educational experience. Keywords: Educational inclusion, diversity, reading corner, inclusive materials